Pengembangan Model Aktivitas Gerak Fisik Anak Usia Dini melalui Permainan Melempar Bola dengan Lagu - Saktiono, Rain Aldi; Rahayu, Tandiyo (Lembaga Yasin AlSys, 2025)
This study aims to increase children's involvement in learning at PAUD LABSCHOOL UNNES, a laboratory school owned by Semarang State University that serves children aged 1-8 years, including children with special needs with mild categories who are assisted by shadow teachers. One of the challenges in learning at this PAUD is the low level of children's focus, because they are more interested in playing than following learning instructions. This study uses the Research and Development (R&D) method with a sample of 10 children per class. The instruments used include gross motor skills, social skills, responses to instructions, and children's level of enjoyment. Data analysis was carried out descriptively as a percentage with a Likert scale. In addition, initial data were analyzed using a normality test, while the final data were tested with a t-test to measure the effectiveness of the intervention given. This study produced a game product Throwing Balls with Songs which aims to train children's concentration and focus to follow instructions in learning games.